Students’ Need Analysis on English Learning Material at Mechanical Metal in SMK N 8 Padang - Hevriani Sevrika (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
Mechanical students need material in English subject that relevant with their department. However, most of the teachersused the materials that are general English to teach English in the mechanical department. Thus, in this research the writer did it toknow the students’ need. In this research, the samples are the students in the mechanical metal department. There are two classeswhich are 45 students. The writer took 15 students through technique sampling is sample random sampling. The instrument thatwriter used to take the data is questionnaires through open – ended questions. The students need in learning English can be seen inthree aspects: necessities, lacks, and wants. The first aspect is necessity, the finding is the students need English materials that are easyto be understood by them. They need the words of the text which are simple and easy to be understood. The second aspect is lack thatthe students’ lacks are they have fewer vocabularies, so they are difficult to understand the texts. The last aspect is wants; they wantto have fluency in speaking so they need to have more activities in speaking skill. Otherwise, the teacher rarely gave speaking skill inteaching and learning process. Thus, the teachers need to know what are the students need to be learned in their departments.